(untitled) (Olhares, 2015)
Improvisation and dramatic play as a procedure for the discovery of significant resources in the field of acting/actor reception/spectator. The text shares the experience in the Workshop of Improvisation by Frank Totino held in July 2010, at the School of Arts Célia Helena, while pointing some reflections on the contemporary improvisation.